Mutations in regulators of the epigenome and their connections to global chromatin patterns in cancer - Plass, Christoph; Pfister, Stefan; Lindroth, Anders M.; Bogatyrëva, Olga; Claus, Rainer; Lichter, Peter (Nature reviews. Genetics, 2013)
Tumour genomes are characterized by extensive alterations that affect the genome as well as the epigenome. Both types of alterations change global gene expression patterns.Novel genome-wide sequencing technologies allow the comprehensive search for genetic and epigenetic alterations. These technologies provide extensive data sets on genes and gene regions that are altered in a cancer genome.Many malignancies show mutations or other chromosomal rearrangements in genes that are responsible for the establishment, maintenance and reading of epigenetic patterns.Epigenetic pathways include DNA methylation, histone modifications and chromatin remodelling.Many tumour genomes carry a specific mutation in a regulator of the epigenome (such as histone H3.3 K27M and isocitrate dehydrogenase 1 (IDH1) R132H mutations) and are characterized by subgroup-specific DNA and histone modification patterns. This suggests that mutations in regulators of the epigenome are mechanistically linked to the altered epigenome.In this Review, we propose a systematic integrative analysis of profiling data to uncover molecular mechanisms that lead to altered epigenomes.Mutations in regulators of the epigenome are attractive targets for epigenetic therapy.